Effects of plyometric training on softer vs. Harder surfaces on jump-related performance in rugby sevens players - Ojeda-Aravena, Alex; Azócar-Gallardo, Jairo; Campos-Uribe, Victor; Báez-San Martín, Eduardo; Aedo-Muñoz, Esteban Ariel; Herrera-Valenzuela, Tomás (Frontiers in Physiology, 2022)
The aim of this study was to compare jump-related performance after plyometric training on harder vs. softer surfaces in rugby sevens players. Fourteen players were randomly assigned into harder surface group (H-G, n = 7) and softer surface group (S-G, n = 7). Three times per week, in the morning, the players performed a plyometric training on different surfaces and strength training in the afternoon. Before and after 4-week intervention period, were assessed with squat jump (SJ), countermovement jump (CMJ), and CMJ with arms (CMJA) tests to measure vertical jump displacement (d), rate of force development (r), and power (p). The main results indicated a significant improvement in S-G for CMJd (∆% = +8.2%; p = 0.029; ES = 0.59) and for CMJAp (∆%= +8.7%; p = 0.035; ES = 0.44). These improvements were significant compared to H-G for CMJAd (F1,12 = 8.50; p = 0.013; η2p = 0.41; ES = 0.83) and CMJAp (F1,12 = 7.69; p = 0.017; η2p = 0.39; ES = 0.79). This study reveals that performance related to countermovement jump with arms on softer surface after 4-week of plyometric training was effective in improving vertical jump displacement and lower body power in rugby sevens players.